Infectious Complications of CD19-Targeted Chimeric Antigen Receptor-Modified T Cell Immunotherapy. (4th October 2017) - Hill, Joshua; Li, Daniel; Hay, Kevin; Green, Margaret L; Riddell, Stanley; Maloney, David; Boeckh, Michael; Turtle, Cameron
Abstract: Background: Lymphodepletion chemotherapy followed by CD19-targeted chimeric antigen receptor-modified T (CAR-T) cell infusion is a novel treatment for refractory B cell malignancies. Infectious complications of CD19 CAR-T cell immunotherapy have not been studied. Methods: We described infections between 0–28 and 29–90 days after CD19 CAR-T cell infusion in patients with relapsed and/or refractory CD19+ malignancies treated in a phase 1/2 open-label trial (NCT01865617). We used Poisson and Cox regression to evaluate pre- and post-CAR-T cell infusion risk factors for infection, respectively. Patients receiving anti-tumor therapy after CAR-T cell infusion were censored. Results: The cohort included 133 patients with acute lymphoblastic leukemia (ALL, n = 47), chronic lymphocytic leukemia (CLL, n = 24), and non-Hodgkin lymphoma (NHL, n = 62). There were 43 infections in 30 patients (22.6%) within 28 days after CAR-T cell infusion with a mean of 1.19 infections per 100 days-at-risk (Fig 1). Among 119 patients followed at our center from day 29–90, there were a mean of 0.67 infections per 100 days-at-risk. Six patients (4.5%) developed invasive fungal infections. Infection was a primary or secondary cause of death in 2 patients (1.5%). Pre-CAR-T cell infusion factors that were associated with more infections included a diagnosis of ALL, >=4 prior chemotherapeutic regimens, and highest CAR-T cell dose (2 × 10 7 cells/kg) ( p values <0.001). After CAR-T cell infusion, severe (grade 4–5) cytokine release syndrome (CRS) was associated with a >3-fold increased hazard for infection ( P < 0.001) and was the primary risk factor. Patients receiving an optimized lymphodepletion and CAR-T cell dose regimen had a mean of 0.74 and 0.63 infections per 100 days-at-risk between days 0–28 and 29–90 with no fatal infections. Conclusion: The incidence of infectious complications after CD19 CAR-T cell immunotherapy was similar to that seen in patients with relapsed and/or refractory B cell malignancies receiving salvage chemoimmunotherapies. Patients with more prior chemotherapy regimens and severe CRS after CAR-T cell infusion had the highest risk for infection. Fatal infections were rare, and patients receiving optimized regimens had fewer infectious complications. Disclosures: D. Li, Juno Therapeutics: Employee and Shareholder, Salary; S. Riddell, Juno Therapeutics: Consultant, Grant Investigator and Shareholder, Research support; D. Maloney, Juno Therapeutics: Grant Investigator, Research support; C. Turtle, Juno Therapeutics: Investigator, Research support